La composition corporelle des adolescentes. La mode et quelques répercussions cliniques - Consuelo Prado; Anders Holt Nielsen; Raquel Martínez; Margarita Carmenate; Cesare Donoso (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The biological and psychological changes which occur during growth stages render children fragile, which can favour risk factors during the period of maturation as well as later on in adult life. The influence of advertising and social pressure is particularly strong in the case of girls, and a new prototype of body proportion has emerged in which extreme thinness is no longer the exception as it has been in previous periods. In order to detect the possible risks and diseases caused by such modifications, 134 adolescent girls in the city of Madrid and its outskirts, aged 15 to 17 years of age, were sampled. The participants understood the objectives of the study and participated voluntarily with parental consent. Two contrasting sub-samples were compared, according to the index of body mass (groups below and above the limit of the somatic tenth percentile, that is BMI = 17). A very low nutritional intake was observed (900 Kcal/day) for the girls with a BMI < 17, as well as a decrease in the recommended proportion of carbohydrates. Irregularity of food intake and risky food-related behaviours were noted. The body composition was modified in comparison to female body norms, which could be the cause of 77% of amenorrhoeas and of androgenicity in fat distribution.